Recent Advances and Design Strategies Towards Wearable Near-Infrared Spectroscopy - Shuoyan Liu; Bing Xue; Wenyuan Yan; Alina Y. Rwei; Changsheng Wu (IEEE Open Journal of Nanotechnology, 2023)
With a growing focus on properties of softness, miniaturization, and intelligence, extensive research has been focusing on constructing wearable electronic devices facilitating comfort, wearable health monitoring and diagnosis. Among recent progress in the development of wearable bioelectronics, wearable near-infrared spectroscopy (NIRS) devices demonstrate wide implementation possibilities in multiple health monitoring scenarios. Throughout the years, multiple design strategies have assisted in developing wearable NIRS devices with high wearing comfortability and miniaturized size. This review summarizes the principle of NIRS technology, recent advances in design strategies towards soft, wearable, miniaturized NIRS devices, and the future potential development directions. Based on the discussion of different design strategies, including modular device design, flexible hybrid electronics, and materials innovation, we also pinpoint some development directions for wearable NIRS. The reviewed and proposed research efforts may enhance the applicability and capability of NIRS as an important technology for digital health.